PENGEMBANGAN MODEL PEMBELAJARAN KOLABORATIF BERBASIS CODING DAN KECERDASAN ARTIFISIAL UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 DI PENDIDIKAN VOKASI TEKNIK - Meiliyanthi, Ina; Purnamawati; Syahrul (Almeera Education, 2025)
Abstract. This study aims to design and develop a collaborative learning model that integrates coding activities and the utilization of artificial intelligence (AI) within technical vocational education as an effort to strengthen students’ twenty-first-century competencies. The research employed a Research and Development (R&D) approach consisting of five core phases: needs analysis, model design, expert validation, limited classroom implementation, and effectiveness evaluation. Data were collected through surveys, interviews, classroom observations, and assessments of students’ competency achievements. The findings indicate that the developed model effectively enhances essential learner competencies, including digital literacy, creative problem-solving, critical thinking, communication abilities, and team collaboration skills. The integration of coding and AI supports learners in deepening their technical understanding, particularly in basic programming, logical analysis, data processing, and the application of intelligent systems to complete project-based tasks. Results from the needs analysis reveal a clear disparity between students’ existing competencies and the technological skills required by industry, reinforcing the necessity of a learning model that combines computational skills with strong collaborative practices. Expert validation provided constructive input regarding the feasibility of the model structure, the suitability of assessment instruments, and the relevance of AI integration within the vocational context. Limited implementation demonstrated measurable improvements in students’ performance, especially in designing technical solutions using coding and operating AI features such as automation, data classification, and intelligent recommendation systems. The final evaluation confirms that the model does not only strengthen learners’ technical capability but also fosters active, contextual, and industry-relevant learning experiences. The integration of this learning model is considered a strategic initiative for addressing the challenges of the Industrial Revolution 4.0 and Society 5.0. The developed model is recommended for broader application and further enhancement within adaptive vocational curricula responsive to future technological advancements. This research contributes significantly to vocational institutions by offering an innovative digital technology based instructional framework. Keywords: Collaborative learning, Coding, Artificial intelligence, Technical vocational education, Twenty-first century skills